O-104 Providing accurate information – impact of ancestry testing. (30th June 2022) - Kirkman-Brown, J; Calhaz-Jorge, C; Dancet, E; Lundin, K; Martins, M; Tilleman, K; Thorn, P; Vermeulen, N; Frith, L
Abstract: Providing information to patients and, or donors at the ART clinic is essential but challenging, especially in the case of reproductive donation. Recent developments in direct-to-consumer genetic testing combined with social media have increased the degree of difficulty. Concepts such as donor anonymity, secrecy and disclosure have to be revisited and totally re-thought as the anonymity of donors, their relatives and also of the children born through donation is no longer guaranteed. This potentially has significant effects on everyone involved: to donors who donated under the assumption that their donation was completely anonymous, to recipients who were under the impression that they could keep donor conception a secret and to donor offspring who were unaware of their donor-assisted conception. It is also effectively retrospective affecting everyone who has, is or might participate. Providing the correct information to donors, ART couples and donor-conceived offspring is the key, and advise for such information provision will be presented in line with the recently published ESHRE good practice recommendations for information provision for those involved in reproductive donation. Trial registration number